Mandatory IFRS Reporting around the World: Early Evidence on the Economic Consequences - DASKE, HOLGER; HAIL, LUZI; LEUZ, CHRISTIAN; VERDI, RODRIGO (Journal of Accounting Research, 2008)
ABSTRACT This paper examines the economic consequences of mandatory International Financial Reporting Standards (IFRS) reporting around the world. We analyze the effects on market liquidity, cost of capital, and Tobin's q in 26 countries using a large sample of firms that are mandated to adopt IFRS. We find that, on average, market liquidity increases around the time of the introduction of IFRS. We also document a decrease in firms' cost of capital and an increase in equity valuations, but only if we account for the possibility that the effects occur prior to the official adoption date. Partitioning our sample, we find that the capital‐market benefits occur only in countries where firms have incentives to be transparent and where legal enforcement is strong, underscoring the central importance of firms' reporting incentives and countries' enforcement regimes for the quality of financial reporting. Comparing mandatory and voluntary adopters, we find that the capital market effects are most pronounced for firms that voluntarily switch to IFRS, both in the year when they switch and again later, when IFRS become mandatory. While the former result is likely due to self‐selection, the latter result cautions us to attribute the capital‐market effects for mandatory adopters solely or even primarily to the IFRS mandate. Many adopting countries make concurrent efforts to improve enforcement and governance regimes, which likely play into our findings. Consistent with this interpretation, the estimated liquidity improvements are smaller in magnitude when we analyze them on a monthly basis, which is more likely to isolate IFRS reporting effects.